Developing Prognostic Competence In Future Teachers: Theoretical Foundations And Pedagogical Conditions - Ikramova Munisa Sheraliyevna (Zien Journals, 2026)
In the context of rapid social transformation, digitalization, and the continuous modernization of education systems, the professional preparation of future teachers requires the development of advanced cognitive and analytical competencies. Among these, prognostic competence-the ability to anticipate, predict, and strategically plan educational processes-occupies a central place. This article examines the theoretical foundations of prognostic competence, its structural components, and pedagogical conditions necessary for its effective development in teacher education institutions. Drawing on constructivist theory, reflective practice models, and competence-based approaches, the study analyzes how problem-based learning, pedagogical modeling, reflective activities, and digital tools contribute to fostering forecasting skills. The paper argues that systematic integration of prognostic tasks into teacher training enhances professional readiness, adaptability, and long-term educational effectiveness
Keywords: prognostic competence; teacher education; professional readiness